Edible Oil Parameters during Deterioration Processes - Marcos Flores; Victoria Avendaño; Jessica Bravo; Cristian Valdés; Oscar Forero-Doria; Vilma Quitral; Yesica Vilcanqui; Jaime Ortiz-Viedma (International Journal of Food Science)
With the continuous increase in research on lipids, technologies and the development of chemical-analytical methods associated with the characterization and monitoring of different processes that involve modifications in edible fats are increasing. The beneficial effect of lipids, especially those essential for the health of the population, is widely known. However, degradation compounds are also produced that eventually have negative effects. In this dual context, the monitoring of the changes suffered by nutritional compounds can be obtained thanks to the development of technologies and analytical methods applied to the study of lipids. The modifications that lipids undergo can be followed by a wide variety of methods, ranging from the basic ones associated with simple chemical titrations to the more complex ones associated with sophisticated laboratory equipment. These determinations involve chemical and/or physical quantification of lipids to know an initial condition on the major and minor components. In addition to technologies that allow monitoring during more complex processes such as thermal deterioration, in multiple conditions depending on the objective of the study, this review could benefit a comprehensive understanding of lipid deterioration for future developments and research in the study of fats and oils for human consumption.